Meta-analisis Penerapan Model Process Oriented Guided Inquiry Learning (POGIL) dalam Pembelajaran IPA - Ikwan Wahyudi (Natural Science, 2022)
This study is a meta-analysis to determine the effect size of the POGIL model in science learning and its variations. Articles were prepared according to PRISMA guidelines based on inclusion criteria. The results of the feasibility assessment set 31 studies for analysis. Meta-analysis was carried out with the CMA program. The effect size is determined by the Hedges' g equation in the random-effects model. The results showed the overall effect size was 1.225 (95% CI [1.028; 1.422]), indicating a positive effect of the POGIL model compared to the conventional model. Analysis of the level of variation resulted in significant differences in the research location and the content of the science material. The variables of education level, media, and types of science learning outcomes did not show significant differences. The results of this meta-analysis show that the POGIL model can be applied to science learning to train students' various thinking skills.